Editorial - Bhalalusesa, Eustella P. (Papers in Education and Development, 2016)
This volume of Papers in Education and Development captures an assortment of both theoretical and research papers focusing on pertinent issues quite topical in the fast changing education scene in Tanzania and beyond. The first paper by Stephen Mabagala sends a compelling message that apart from focusing more on reading and arithmetic, parents, caregivers and schools should allow children to engage themselves in playful activities since these activities help children to learn and develop to their full potentials. The second paper by Ibrahim Nzima illuminates the tutors ' understanding of competence-based curriculum (CBC) from the Tanzanian context. Teachers are change agents and knowing how they conceprtualise CBC as a new form of curricula policy may inform the development of a well-informed teacher education programmes at pre-service and in-service levels.